Rancang Bangun Sistem Monitoring Ketinggian Muka Air Laut Menggunakan Arduino Pro Mini dan NodeMCU ESP8266 - Melvi, Melvi; Ulvan, Ardian; Sidiq, Muhamad Rijal; Batubara, Mona Arif Muda (Penerbit Goodwood, 2023)
Purpose: This study aims to develop and implement a real-time sea water level monitoring system to anticipate high wave hazards, particularly in coastal areas such as Ketapang Pier, Pesawaran Regency, Lampung Province. Research methodology: The system utilizes an IoT-based approach involving an SRF04 ultrasonic sensor for water surface measurement, an Arduino Pro Mini for data processing, a NodeMCU ESP8266 for server connectivity, a DS3231 RTC for time accuracy, and a microSD card module for offline data storage. The system is powered using a 12V adapter regulated through an LM2596 module. Results: Field testing demonstrated that the system accurately records water level distances with an average relative difference of 0.205% between Blynk App and SD Card outputs. The system classifies water levels into two status categories: normal and hazard. Conclusions: The implemented monitoring instrument functions reliably in real-time conditions and offers accurate water level readings, making it suitable for coastal hazard early warning systems. Limitations: The system is dependent on continuous power and stable internet connectivity; thus, functionality may be affected in remote or offline environments. Contribution: This research provides an affordable and accurate IoT-based water level monitoring solution that can be replicated in other coastal areas for disaster risk reduction and environmental monitoring.